Cyprus in the Neolithic and Chalcolithic Periods – Cyprus in the Early Bronze Age – Cyprus in the Middle Bronze Age – Cyprus in the Late Bronze Age - Catling, H. W. (1966)
Cyprus in the Neolithic and Chalcolithic Periods (= САН I IX (c)) – Cyprus in the Early Bronze Age (= САН I XXV (b)) – Cyprus in the Middle Bronze Age (= САН II 1V(c)) – Cyprus in the Late Bronze Age (= САН II XXII(b) = fasc. 43).